Himantura hortlei n. sp., a new species of whipray (Myliobatiformes: Dasyatidae) from Irian Jaya, Indonesia - Last, Peter R.; Manjaji-Matsumoto, Mabel; Kailola, Patricia J. (Zootaxa, 2006)
The Indo-Malay region, which is represented by at least 17 whiprays of the genus Himantura, has the richest dasyatid fauna of any region. Himantura hortlei n. sp. is described based on specimens from coastal marine and estuarine habitats in the Arafura Sea off Irian Jaya (southwestern New Guinea). The mature male holotype was caught in the estuary of the Minajerwi River. It is a moderately large ray that reaches at least 0.7 m disc width and 2.4 m total length. This species can be distinguished from most of its congeners by the combination of a relatively narrow, heart-shaped disc with a very long angular snout, very small eyes, a non-protrusible mouth, no deep circumoral grooves, larger and more slowly developing denticles, a less well-developed lateral prepelvic process, a yellowish ventral surface when fresh, denticles present along the upper anterior snout margin, and a denticle band ending well forward of the eyes in adults.